A development of a conceptual model of occupational patterns promoting alcohol abstinence among northeastern Thais with alcohol use disorder - Boonphirom, Rapeepat; Tanimura, Atsuko; Phadsri, Supaluck (Journal of Associated Medical Sciences, 2026)
Background: The difficulty of alcohol abstinence and recovery from unhealthy living patterns is influenced by individual context. There is still limited evidence to reveal concepts and processes of sustained alcohol abstinence in people with experienced alcohol use disorder, including Northeastern Thais. Objectives: This study aimed to develop a conceptual model explaining how Thais with alcohol use disorder in the northeastern region sustain their alcohol abstinence. Materials and methods: Charmaz’s constructivist grounded theory guided the development of a conceptual model. Data collection was done in Khon Kaen, Thailand. Fourteen participants who had sustained alcohol abstinence for at least one year voluntarily participated in semi-structured, in-depth interviews between December 2024 and December 2025. Constant comparative analysis was used on 27 transcripts, 23 observation notes, and memos. Co-researchers rechecked and agreed on the substantive model, and two participants confirmed their data in the model to strengthen trustworthiness. Results: The conceptual model of a healthy pattern promoting alcohol abstinence was developed with four themes interlinking sequentially: acceptance of alcohol addiction, anchoring a better life’s goal, shifting identity formation, and self-determination on a health pattern. The first two concepts indicated initial awareness of the negative impacts of alcohol addiction, then the others emphasized maintaining the determination of a healthy routine without alcohol. Conclusion: All concepts emerged from the first-hand experiences of alcohol abstinence, guided the development of a health pattern promoting sustained abstinence related to the context, and provided ideas for the healthcare providers in further development of a supportive clinical program to prevent addictive relapse.